Strengthening the Role of the Village Children’s Forum and Socialization of the Learning Harmonization Program as an Effort to Reduce the Early Marriage Rate in Lembengan Village - handayani, ririn; Lifchatullaillah, Endang; Lawado, Irma Sahvitri (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2026)
Early marriage remains one of the social issues faced in various regions. Factors that can influence the occurrence of early marriage include limited knowledge about reproductive health, cultural influences, and economic factors. The Village Children’s Forum, as a platform for children’s participation, has a strategic role in reducing early marriage rates, disseminating information, and acting as both pioneers and reporters in the protection of children’s rights. The Learning Harmonization Program is an innovative effort that integrates community-based education with strengthening youths’ understanding of children’s rights, gender equality, reproductive health, and the importance of continuing education. The purpose of implementing this activity is to increase the capacity and active role of the Village Children’s Forum (FAD) in preventing early marriage and to socialize the Learning Harmonization Program to all youth and community members as a means of educating them on children’s rights, reproductive health, and gender equality. The activity is carried out by providing training to all FAD participants and applying the knowledge gained through the Socialization of the Learning Harmonization Program. This community service activity was attended by all 18 members of the FAD. The results of the activity include increased empowerment of the partners in terms of management and community social aspects. Through this training, it is expected that FAD Lembengan will become a driving force in educating peers, encouraging community awareness, and significantly reducing early marriage rates.